Analisis Website Siakad Universitas Janabadra Menggunakan Metode UAT - Fitriastuti, Fatsyahrina; Putri, Annisa Eka; Sunardi, Annisa Kautsar; Hidayat, Regina Apriliya (Jurnal Teknologi Sistem Informasi, 2024)
This research aims to comprehensively investigate and analyze the Janabadra University Academic Information System (Siakad) Website by applying the UAT (User Acceptance Testing) Method. This method is used as a framework to evaluate the level of user satisfaction with various aspects of the functionality, security, reliability and responsiveness of the Siakad website. The research involved collecting data through various approaches, including participant observation, in-depth interviews with active Siakad users, and distributing structural questionnaires. The results of an in-depth analysis of the usability dimensions include navigation, information structure, and user interface, while the security and reliability dimensions highlight aspects of data security and system availability. Website responsiveness is also analyzed to ensure optimal accessibility. The findings of this study provide a detailed picture of the strengths and potential for improvement in Siakad. The implications of the findings can serve as a basis for decision makers and developers to make specific improvements, ensuring that Siakad not only meets user expectations but also adheres to high security and performance standards. This study makes a significant contribution in the context of developing academic information systems in higher education institutions, illustrating the importance of the UAT Method approach as an effective evaluation tool. The findings of this research provide a detailed picture of the strengths and potential for improvement in Siakad. The implications of the findings can serve as a basis for decision makers and developers to make specific improvements, ensuring that Siakad not only meets user expectations but also adheres to high security and performance standards. This study makes a significant contribution in the context of developing academic information systems in higher education institutions, illustrating the importance of the UAT Method approach as an effective evaluation tool